Context-aware environments for online dispute resolution - Novais, Paulo (2012)
Virtual environments, such as Online Dispute Resolution, don’t have the rich context of traditional environments do. We are developing a computational environment that can better support the decision-making process of experts by providing access to meaningful context information, allowing the intervenor to take better supported decisions. The resulting system is able to transparently acquire information about user’s state, including stress or conflict resolution style.